Right Caputo Fractional Landau Inequalities - Anastassiou, George A. (Sarajevo Journal of Mathematics, 2024)
Right Caputo fractional · _p-Landau type inequalities, p( 1,∞ ] are obtained with applications on R_-. 2000 Mathematics Subject Classification. 26A33, 26D10, 26D15